Neurorestorative and protective effects of palmitoylethanolamide in perinatal asphyxia: An analysis of the rat striatum - Udovin, Lucas (2018)
Perinatal asphyxia (PA) caused by low O2 availability during birth is associated with brain damage, been the striatum one of the most affected areas. Palmitoylethanolamide (PEA) is a neuroprotective amide in brain injury models, including PA. However, its effects against PA requires deeper study in the striatum. Using Bjelke? model, full-term pregnant rats were rapidly decapitated, and uterus horns placed in a water bath (37°C,19 min). One hour after, rats were treated with PEA (10 mg/kg,s.c.) and later given to surrogate mothers. 30d animals were perfused and coronal striatum sections as well as subcellular fractions were collected for immunohistochemistry and blotting (n=3). Phosphorylated high/medium molecular weight neurofilaments (pNF-H/M), Microtubule-Associated Protein 2 (MAP2), and Glial fibrillary acidic protein (GFAP) were analysed. All procedures were previously approved by our Institution. 2-way ANOVA followed by Tukey revealed a reduction in pNF-H/M and MAP2 reactive areas (45% and 70%), GFAP+ cells (20%) and reduced MAP2 and pNF-H/M immunocontents in PA-rat striatum. PEA totally restored GFAP+ cells and MAP2 immunoreaction and partially prevented the decreased pNF-H/M reactive area (78%) induced by PA. PEA also reversed the MAP2 reduction and partially prevented the decrease of pNF-H/M immunocontent induced by PA. No GFAP level alteration was detected. PEA treatment attenuated the striatum damage induced by PA, demonstrating its therapeutic potential against PA.